The Need for Cosmopolitan Responsibility in Platform Capitalism Companies - Lopes Saldanha, Jânia Maria; dos Santos Witschoreck, Pedro Victor (Perfiles de las Ciencias Sociales, 2023)
The article proposes to study, in the context of globalization and transnationalization of economic relations, platform capitalism, especially the definition of this scenario, considering the logic of transnational companies that operate in this field, especially regarding labor uberization. The objectives are to a) investigate platform capitalism as a source of autonomy for workers; b) study the concept of labor uberization; c) analyze platform capitalism in the logic of transnationality; d) investigate corporate "cosmopolitanism of responsibility" for an alternative to combat the informalization of platform labor. The research problem driving the article is the following: considering 21st century platform capitalism, is it possible to find ways in the juridical cosmopolitanism of responsibility to hold responsible transnational companies operating on a platform? A dialectical approach is used, exposing contradictions causing the insecurity of the worker inserted in this environment, by means of bibliographic and documental research. The conclusion states it is urgent to formulate legislation in a global sense to deal with local problems that become universal, precisely because of the lack of an internationalized treatment of the subject. Furthermore, domestic legislations themselves must adapt to the impacts of the network society, seeking to hold transnational companies locally responsible, though bound to the global legal treatment of the issue through responsible cosmopolitanism.